PENDEKATAN HERMENEUTIK DALAM PEMAHAMAN HADIS (Kajian Kitab Fath al-Bari Karya Ibn Hajar Al-‘Asqalani) - Yahya, Agusni (Ar Raniry : International Journal of Islamic Studies, 2014)
The hadith explanation book of Sahih al-Bukhari written by Ibn Hajar Al-‘Asqalani, Fath al-Bari, is one of the most pupular books in Moslem ummah. Is widely used by Moslem scholars to meet the meanings of hadiths compiled by the imam al-Bukhari in his Sahih al-Bukhari. Fath al-Bari is considered significant to do the research on it in order to develop the science of hadith, mainly through the hermeneutic method. By using this method, the research questions are: 1. How does Ibn Hajar Al-‘Asqalani explain the matans (hadith texts) of Sahih al Bukhari in connection with hermeneutic method? 2. What are the hermeneutic principles used by Ibn Hajar Al-‘Asqalani in his explanations of hadith? This research is expected to respond the research questions above so that it can be implimented the field of hadith in relation to develop hadith methodology. Finally, the research uncover that in his explanations of hadiths, Ibn Hajar Al-‘Asqalani is oriented his world views to the classical Islam, the era of Prophet’s companions and their successors, the Salaf al-Salih. He does not express the Islamic world issues available in his time in his explanations of the hadiths. He is considered a normative ‘ulama since he is not influenced by the emerging cases situated his time in Egypt, Mecca and Madina. He tends to be textual to explain the matans of hadiths although to some extent he uncovers the historical contexts of the hadiths he explains. This is common for a muhadith whose main jobs is to collect and narrate the whole data on Prophet's sayings, acts and permissions either on sanads (narrators) or matans (texts).Keywords: Fath al-Bari; sharh al-hadith; hermeneutik.